In vitro CAPE inhibitory activity towards human AKR1C3 and the molecular basis. (25th June 2016) - Li, Cuiyun; Zhao, Yining; Zheng, Xuehua; Zhang, Hong; Zhang, Liping; Chen, Yunyun; Li, Qing; Hu, Xiaopeng
Abstract: AKR1C3 is a critical enzyme for producing testosterone and 5α-DHT in the human body. Inhibiting AKR1C3 is a potential target for treating castration-resistant prostate cancer (CRPC). To find AKR1C3 inhibitors with a new molecular skeleton and binding mode, we analyzed the in vitro inhibitory activity of caffeic acid phenethyl ester (CAPE) and eight other phenolic acid analogues towards AKR1C3 and six other human AKR1 enzymes. We analyzed CAPE and octyl gallate interactions with AKR1C3 using X-ray crystallography, which provided a molecular basis for understanding the phenolic acid inhibitory activity and selectivity towards human AKR1s. Highlights: In vitro inhibition of CAPE and eight other analogues towards 7 human AKR1 enzymes. CAPE selectively inhibits AKR1C3 with the highest IC 50 (3.71 μM). The structural basis of CAPE and AKR1s interactions is described.